Female Power in Education: Is it a Reversal of Gender Gap? - Bouchaib Benzehaf (Yayasan Visi Intan Permata, 2017)
Education today is increasingly being feminized with girls accounting for the large majority of the student population at all levels. This feminization is happening not only in terms of number of girls but also in terms of performance. The present paper reports on a comparative study that looked into the differences between girls’ achievements and boys’ achievements in high education. More specifically, the paper explores gender differences in written linguistic proficiency by analyzing a sample of high school students’ pieces of writing in English. The research sample consisted of 130 high school students in the city of El Jadida, 59 males and 71 females. Using Hunt’s T-units as a method of language measurement, the paper outlines gender differences in the sample in terms of accuracy, fluency and complexity. Results showed that girls significantly outperformed boys in different aspects of writing, thereby suggesting a reversal of gender inequality. However, care must be taken so that these differences which favor girls are not misinterpreted in such a way as to reproduce traditional gender inequalities in educational institutions (for instance, some people are advancing the idea that boys are differently, not deficiently, literate). In light of the results, the paper ends with recommendations for justice to be done to female students as well as for the adoption of best classroom management practices that maximise all students’ achievements.